RESISTENSI UMKM MELALUI GOOD GOVERNANCE PADA PELAKU USAHA DI DESA EKANG ANCULAI - Yanto, Meidi; Fatahuddin, Fatahuddin; Basyid, Abdul; Wikar, Muhammad Aldifa; Nurasikin, Dini; Fazila, Fatwa; Satya, Hardi; Indarti, Wiwin (P3M STIE Pembangunan Tanjungpinang, 2025)
This writing describes the community service program, especially for Micro, Small and Medium Enterprises in Ekang Anculai Village, which is currently still underdeveloped. It should be that with the development of technology, this should bring fresh air to business actors in maintaining the resistance of their businesses in society. The purpose of carrying out this activity is to help MSMEs in Bu Santi's shop located in Hamlet 1, Ekang Anculai Village, Telok Sebong District, Bintan Regency in running their business. The method used in this activity is the method of observation and interviews. The activities that the service team carried out during the service were carried out and were successful. The service team made improvements to the UMKM Warung Bu Santi by updating the appearance of the UMKM by painting the stall, installing banners, making a physical menu and updating tablecloths so that local people were interested in visiting UMKM. That way the service team hopes that the business actor, namely Mrs. Santi's shop, will continue to maintain the business they have.